Exudation of organic acid anions by tropical grasses in response to low phosphorus availability - Almeida, Danilo Silva [UNESP]; Delai, Lucas Benes [UNESP]; Helena Frankland Sawaya, Alexandra Christine; Rosolem, Ciro Antonio [UNESP] (Nature Research, 2020)
It has been suggested that some tropical grasses can acquire phosphorus (P) from hematite and gypsite by exuding organic acid anions (OAs). However, it remains to be determined exactly which OAs could be involved in each case. The objective of this study was to verify the exudation OAs by ruzigrass (Urochloa ruziziensis), palisade grass (U. brizantha), and Guinea grass (Megathyrsus maximus) as a response to P deficiency. The grasses were grown in leachate columns with adequate and deficient P nutrient solutions. The concentration of OAs in the leacheate and root surface, as well as shoot and root dry matter, and P uptake were determined. Citrate, isocitrate, and malate concentration in leachates and root surfaces increased with P starvation, mainly for the Urochloa grasses. Oxalate exudation was similar for the grasses under adequate P supply, but was lower in Guinea grass under P starvation. Palisade grass showed a higher concentration of total OAs in the root surface than the other species due to a great production of oxalate and isocitrate. Palisade grass showed greater dry matter yields regardless of P deficiency, and Guinea grass always had the higher shoot:root ratio. Urochloa grasses have a higher capacity to cope with low P availability by exuding OAs along with a lower shoot:root ratio than Guinea grass.